2021
DOI: 10.31764/jtam.v5i1.3776
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Students’ Errors in Completing Essay HOTS Questions Based On Watson's Criteria Viewed From The Cognitive Style Perspective

Abstract: This study aimed to determine the students’ errors classified as Field Independent (FI) and Field Dependent (FD) in solving essay HOTS questions based on Watson criteria and to find out the causes of errors experienced by FI and FD types of students in finishing those questions. This was qualitative research which implemented the case study method. This research was carried out at Junior High School 3 Kepanjen Malang of 2019/2020 academic year. Research subjects were determined based on The Group Embedded Figu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This is in line with the results of research by [16] which revealed that one of the factors causing students to experience difficulties in solving problems is that they are not careful when working on problems so that many students make mistakes when carrying out elimination, substitution and algebraic operations in addition and subtraction. This is also in line with the research results of [17] which stated that one of the reasons why students find it difficult to solve problems is because students are not careful in solving problems that have a lot of arithmetic operations in them.…”
Section: Description Of Students' Difficulties In Solving Problem Numbersupporting
confidence: 86%
“…This is in line with the results of research by [16] which revealed that one of the factors causing students to experience difficulties in solving problems is that they are not careful when working on problems so that many students make mistakes when carrying out elimination, substitution and algebraic operations in addition and subtraction. This is also in line with the research results of [17] which stated that one of the reasons why students find it difficult to solve problems is because students are not careful in solving problems that have a lot of arithmetic operations in them.…”
Section: Description Of Students' Difficulties In Solving Problem Numbersupporting
confidence: 86%
“…While research (Sanwidi, 2018) stated that the factors that cause students to give illogical reasons are used in explaining problem solving and are in a hurry because of time. The same thing happened in research (Santoso, Cholily, & Syaifuddin, 2021) the one who manipulated the calculation is applying the wrong formula so that the answer given is also wrong.…”
Section: Discussionmentioning
confidence: 97%
“…The problems found at the Senior High School (SMA) level from student factors include students needing to be more active in learning activities. (Lestari & Putri, 2020), Students find it difficult to express opinions (Sari et al, 2018), students do not understand the concept (Apriliani et al, 2016), students have difficulty performing arithmetic operations (Eriyanti et al, 2022b;Santoso et al, 2021), Students are not careful when working on questions. Apart from that, the problems found were a decrease in learning motivation and learning concentration, which impacted learning achievement; students were less accustomed to solving problems, and students' learning independence still needed improvement (Fauza et al, 2022;Schukajlow et al, 2022).…”
Section: Problems Of Mathematics Learning In High Schoolmentioning
confidence: 99%